Os Pyhcop Cati ji, a necropolítica e os processos de resistência - Pereira, Juliana Martins (2021)
This ethnography was elaborated from an affective experience with the Pyhcop Cati ji who live in the Indigenous Territory of Governador, located in the transamazonian region of Maranhão. Its objective is to describe the State's colonial strategies as necropolitical, which administratively encouraged a local non-indigenous occupation by fomenting an extractivist and cattle-ranching economy through the use of development projects. This occupation of the surrounding territory is marked by conflicts and enmities created by a rhetoric that situates the indigenous people as enemies of the nation and of development, generating a hate and racism speech against them. In this way, some concepts that are developed were discussed in order to reflect on the instrumentalization of the death of the Other, the one placed in a condition of maximum otherness. Finally, this work attempted to address the resistance of these indigenous people against the colonial advance over their lands, according to their own cosmology, which has the body as its central point. The political ontology and the way of existing and inhabiting the territory are great powers of resistance that cross more than five hundred years of genocide, preserving a way of living and building the body.